A metal-organic framework@hydrogen-bond framework as a matrix for MALDI-TOF-MS analysis of small molecules. Issue 47 (20th May 2022) - Yin, Shi-Jun; Zheng, Guo-Can; Yi, Xin; Lv, Guang-Ping; Yang, Feng-Qing
Abstract : A hydrogen-bond framework and metal-organic framework composite (MOF@HOF) is prepared and used as a matrix for the analysis of small-molecule compounds by MALDI-TOF-MS. Abstract : A novel MOF@HOF composite that can serve as a matrix for analysis of small molecules by MALDI-TOF-MS was fabricated through a simple solvothermal method. Taking falvonoids as an example, this composite/matrix presents high desorption/ionization efficiency, low background interference, high salt tolerance, and satisfactory signal reproducibility for MALDI-TOF-MS analysis.